(3GdHMK GdYdej hefGgLg aj GdYdhe GdELJeGYjI hGdSdhcjI (B/s - (3cTQhO, YeGQ GdWjHs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2006)
(3GdHMK GdYdej(B: (3JYQja GdHMK GdYdej hJMOjO eGgjJg, cjajI GNJjGQ GdehVhY hJMOjO eTcdJg, WQb GdMUhd Ydi GdeYQaI, GdaQhV GdYdejI, GdYjfGJ hWQb GNJjGQgG, COhGJ GdHMK GdYdej heUGOQg, efGgL GdHMK GdYdej(B: (3GdefgL GdhUaj, GdefgL GdJLQjHj, efgL OQGSI MGdI, GdefgL GdJGQjNj, GdGbJHGS hGdJhKjb hcJGHI GdHMK(B: (3GdGbJHGS hGdJhKjbs
(3HHdjhZQGajG(B: (3U(B.367s
Keywords: (3GdHMhKs; (3GdeYQaIs